Lured by Likes: Evaluating the Online Visibility of Predatory Journals through Altmetric Indicators - C, Vysakh; K P, Muneesa (Journal of Data Science, Informetrics, and Citation Studies)
The purpose of this study is to evaluate the influence of questionable journals on social media. Now defunct and apparently western-biased Beall’s List was used to identify predatory journals mostly from the non-western countries, and Altmetric Explorer was used to extract the social media attention. The results showed that Beall’s list had 1,310 predatory journals as of March 2025, and 7,873 articles from 77 deceptive journals garnered web attention from various social media platforms, with a total Altmetric Attention Score (AAS) of 37,427. The low intake of predatory articles on social media can be considered as a parameter in identifying the deceptive journals. Predatory journals were present on 18 different platforms, with a higher presence on Mendeley, accounting for 234467 (88.13%) mentions, and Twitter, with 20949 (7.87%) mentions. The articles from the journal "Aging" received the highest social attention, with 54,748 mentions for its 4,720 articles. The geographical results showed that web discussions about the questionable articles were predominantly from English-speaking countries, including the United States, the United Kingdom, and Canada. Finally, the study reported a significant, weak positive correlation between Dimensions Citation (DC) and altmetric attention score, with a correlation coefficient value of 0.23 (rho = 0.23, p ≤ 0.001) for the articles. The present study offers valuable insights for the entire research community on utilising altmetrics as a reliable indicator for identifying predatory journals.
Keywords: Predatory Journals; Questionable Journals; Deceptive Journals; Altmetrics; Social Media Attention; Research Misconduct.